Biomolecular Data Science—in Honor of Professor Philip E. Bourne (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint includes 14 articles in Biomedical Data Science in honor of Professor Philip Bourne. Contributed by world-renowned experts, these articles cover a broad range of topics in machine learning, biophysics, bioinformatics, and systems biology.